2019
DOI: 10.1001/jamanetworkopen.2018.7765
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Population Comparisons of Surgery and Radiotherapy Outcomes in Prostate Cancer Using Bayesian Multistate Models

Abstract: This cohort study uses Bayesian multistate models for a unified statistical approach to compare the association of surgery and radiotherapy with both metastatic clinical failure and survival in men with localized prostate cancer and develops an online calculator for individualized treatment-specific outcome prediction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 54 publications
(91 reference statements)
0
25
0
1
Order By: Relevance
“…Patients undergoing radiotherapy are usually older, have more co-morbidities and a more aggressive disease [26]. When developing individualized prediction models for the outcomes (relapse or death), some patient characteristics are associated with different treatment-related outcomes, for example reduced mortality rate in patients with elevated Gleason score choosing EBRT, whereas patients with perineural invasion fared better following surgery [26]. Nevertheless, there is a difference in long-term side-effects between the different treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Patients undergoing radiotherapy are usually older, have more co-morbidities and a more aggressive disease [26]. When developing individualized prediction models for the outcomes (relapse or death), some patient characteristics are associated with different treatment-related outcomes, for example reduced mortality rate in patients with elevated Gleason score choosing EBRT, whereas patients with perineural invasion fared better following surgery [26]. Nevertheless, there is a difference in long-term side-effects between the different treatments.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, traditional therapeutic approaches have consisted of hormonal therapy, chemotherapy, bisphosphonates, and best supportive care [17][18][19] . The large number of studies accomplished to evaluate the oncological outcomes among PCa patients treated with RP or EBRT have brought conflicting results [20][21][22] . Many evidences obtained from retrospective cohorts have suggested that patients with locally advanced disease could take advantage of active treatment and those subjected to RP should have reduced risk of secondary involvement 23,24 .…”
Section: Management Of Mcrpcmentioning
confidence: 99%
“…Moreover, in the case of localized PCa, the oncologic follow-up is strongly favored by serum PSA dosage, that after RP must be undetectable in the absence of disease relapse 3 . On the other hand, EBRT is a therapeutic option with a radical purpose for localized PCa treatment commonly reserved for older patients, or for patients with comorbidities that contraindicate a major surgical procedure, or in those that prefer to avoid the most frequent side effects caused by surgery, as urinary incontinence and erectile dysfunction 21 . Recent clinical trials 20 Conversely, in advanced stages, EBRT alone appears to be insufficient and therefore patients will need multimodal therapy in a multidisciplinary framework 29 .…”
Section: Rp Vs Ebrt: a Challenging Choicementioning
confidence: 99%
“…There was heterogeneity in patients' characteristics as our study was not randomized. Patients undergoing radiotherapy are usually older, have more co-morbidities and a more aggressive disease (26).…”
Section: Discussionmentioning
confidence: 99%
“…When developing individualized prediction models for the outcomes (relapse or death), some patient characteristics are associated with different treatment-related outcomes, for example reduced mortality rate in patients with elevated Gleason score choosing EBRT, whereas patients with perineural invasion fared better following surgery (26). Nevertheless, there is a difference in long-term side-effects between the different treatments.…”
Section: Discussionmentioning
confidence: 99%